Effectiveness of Emotion-Focused Therapy and Schema Therapy on Attachment Styles and Emotion Regulation in Women Affected by Infidelity - Tahavvori, Zohreh; Lashgari, Mahdi; Taher, Mahboobeh (Applied Family Therapy Journal (AFTJ), 2025)
Objective: The present study aimed to examine and compare the effectiveness of emotion-focused therapy and schema therapy on attachment styles and emotion regulation in women affected by infidelity. Methods and Materials: This research employed a quasi-experimental design with a pretest–posttest and control group. The statistical population included all women affected by infidelity who referred to counseling centers in Tehran in 2023. From this population, 45 participants were selected using purposive sampling and randomly assigned to three groups: the first experimental group (emotion-focused therapy, 15 participants), the second experimental group (schema therapy, 15 participants), and the control group (15 participants). The experimental groups received the respective interventions across a set number of sessions, while the control group did not receive any intervention. All three groups were assessed at pretest, posttest, and follow-up stages using the Attachment Styles Questionnaire and the Emotion Regulation Questionnaire. Findings: Data analysis using repeated measures analysis of variance and post hoc tests indicated that both therapeutic approaches led to significant improvements in attachment styles and enhanced emotion regulation abilities in women affected by infidelity (p < .05). Moreover, a comparison of results showed that schema therapy demonstrated greater effectiveness than emotion-focused therapy in certain indices. Conclusion: Based on the findings, emotion-focused therapy and schema therapy can be considered effective approaches for promoting secure attachment styles and improving emotion regulation among women affected by infidelity.